2018
DOI: 10.1007/978-1-4939-7614-0_17
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Assessment in Clinical Studies of Substance Use Disorder

Abstract: The therapeutic effect of exercise in promoting mental health is well known, and there is a growing body of evidence for incorporating physical activity-based interventions in the management of substance use disorders (SUD). A particular challenge in this area is a lack of standardized testing protocols between studies and clear descriptive statistics on the capacity of the SUD patient to perform exercise. Therefore, an essential starting point for new studies that seek to incorporate exercise into usual care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A previous meta-analytic study (Wang et al, 2014 ) demonstrated PA to be an effective tool in SUD therapy. However, the benefits of PA on SUD treatment outcomes has not yet been fully proven (Linke & Ussher, 2015 ; Zschucke et al, 2012 ) due to a lack of standardized program methodology and program heterogeneity (Dowla et al, 2018 ) and inconsistent evaluation criteria (Colledge et al, 2018 ). However, positive effects of PA have been observed with short- or long-term exercise programs (Brown et al, 2016 ; Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analytic study (Wang et al, 2014 ) demonstrated PA to be an effective tool in SUD therapy. However, the benefits of PA on SUD treatment outcomes has not yet been fully proven (Linke & Ussher, 2015 ; Zschucke et al, 2012 ) due to a lack of standardized program methodology and program heterogeneity (Dowla et al, 2018 ) and inconsistent evaluation criteria (Colledge et al, 2018 ). However, positive effects of PA have been observed with short- or long-term exercise programs (Brown et al, 2016 ; Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exercise assessments will include a modified three-minute step test to evaluate cardiorespiratory fitness, the ACSM 3-minute curl up test and push up to fatigue to assess muscular endurance, a balance error scoring system test to assess balance, hand grip dynamometer to assess general body strength and a 6-minute walk test and sit to stand in 30 seconds to assess functional capacity. 19,20…”
Section: Secondary Outcomesmentioning
confidence: 99%